(untitled) (Jurnal Arsitektur ARCADE, 2026)
Kampung Kauman Yogyakarta is a traditional settlement established in 1773 as a residence for religious palace servants, featuring architecture that results from the acculturation between Javanese cultural values and Islamic teachings. This study aims to reveal the spatial structure of traditional houses in Kampung Kauman through space syntax analysis of 15 sample houses. The method employed is convex space analysis (Hillier & Hanson, 1984) using parameters of Total Depth (TD), Mean Depth (MD), and Relative Asymmetry (RA). The findings identify a spatial genotype in the form of a consistent three-room linear pattern across all houses: Pendhopo (public space, RA 0.148–0.273), Pringgitan (transition space, RA 0.080–0.220), and Dalem (private space, RA 0.091–0.127). The analysis reveals a mathematically measurable privacy gradient from public to sacred space (Senthong, RA 0.745). Differences among house types (A, B, C) indicate erosion of spatial hierarchy with physical changes. This study concludes that the spatial structure of Kauman houses has a consistent relational pattern a spatial genotype or three-room linear pattern where the preservation of traditional architecture must maintain the entire system of spatial relationships, not merely physical forms.